PENGARUH MANAJEMEN RANTAI PASOKAN DAN MANAJEMEN MUTU TERPADU TERHADAP KINERJA PT UNIRAMA DUTA NIAGA CABANG BEKASI - Sari Mariana; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
The rapid development of retail in Indonesia makes it important to have a good product distribution so that it is fast and right into the hands of consumers. Thus, in meeting customer satisfaction, it is necessary to implement supply chain management and total quality management in improving company performance. This study aims to analyze the influence of supply chain management which consists of integration of suppliers and distributors, reducing suppliers, partnerships and procurement sources, for total quality management consisting of focus on customers, continuous system improvement, education and training, teamwork, obsession with quality, involvement employees, scientific approach, restrained freedom, long term commitment and unity of purpose. The data used is primary data obtained directly from all employees of PT Unirama Duta Niaga Bekasi branch as respondents. The data analysis method used in this research is descriptive analysis and multiple regression analysis. The results of this study indicate that supply chain management and total quality management together have a positive and significant influence on company performance at PT Unirama Duta Niaga Bekasi branch, the hypothesis is that "there is a significant positive influence on the role of supply chain management and total quality management on company performance has been proven".